Healthy housing as social determinant of health: international and national experiences - Mara Rejane Barroso Barcelos; Telma Abdalla de Oliveira Cardoso; Sandra Conceição Ferreira Monteiro; Débora Cynamon Kligerman; Simone Cynamon Cohen (Revista Brasileira em Promoção da Saúde, 2011)
Objectives: To promote a reflection on the problem of the evolution of the city and the existence of a technological paradigm, for despite the knowledge of technologies, they are not accessible to the entire population. It also discusses the need to build healthy housingand how these translate into social determinants of health. Data Synthesis: A literature review based on the themes “healthy housing” and “social determinants of health” to present the experiences of the programs Red Interamericana de la Vivienda Saludable (Red VIVSALUD) and Rede Brasileira de Habitação Saudável (Brazilian Network for Healthy Housing). The program, developed since 1995 by Red VIVSALUD, an international initiative of the Pan American Health Organization and the precursor of healthy housing initiative, is effective in Brazil through the Brazilian Network for Healthy Housing. This network has become a movement to incorporate human resources training, development of research with community participation and interventions through the dissemination of the concept and practice of health promotion policy within the housing. Conclusion: With the development of urban space, there is a significant deterioration in quality of life due to lack of health infrastructure, shortage of housing and health inequalities. A healthy housing mentions to a space characterized by a set of conditions that influence the processes of restoration, protection and health promotion. Its construction will be successful if the initiative is embedded in programs and projects of housing and urban development, undertaken bygovernments.